Job Crafting and Role Ambiguity in Adaptive Performance: The Parallel Mediating Roles of Self-Efficacy and Resilience Among Indonesian Educators - Azam Makarim; Muzakar Isa; Jati Waskito (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The increasing complexity of Islamic educational institutions requires educators and educational staff to demonstrate a high level of adaptability in responding to changing organizational demands and overlapping job roles. This study tests a dual parallel mediation model, in which self-efficacy and resilience act as mediators in the relationship between job crafting, role ambiguity, and adaptive performance. The study aims to address the lack of empirical evidence regarding the psychological mechanisms underlying adaptive performance among educators and educational staff in Islamic educational institutions in Indonesia. Employing an explanatory, cross-sectional quantitative design, this study gathered data through a structured survey completed by 152 PTK members drawn purposively from six private Islamic schools in Polokarto Sub-district, Sukoharjo Regency. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The results indicate that job crafting has a positive and significant effect on self-efficacy, resilience, and adaptive performance. Conversely, role ambiguity had a direct negative effect on adaptive performance, while its indirect effects via self-efficacy and resilience were not found to be significant. Furthermore, self-efficacy and resilience fully mediated the relationship between job crafting and adaptive performance, with resilience emerging as the strongest mediator (f² = 0.368). This study contributes to the development of the literature by integrating Social Cognitive Theory and the Job Demands–Resources Model into a single conceptual framework, while also affirming the central role of psychological resources in enhancing adaptive performance within the context of Islamic educational institutions in non-Western countries. Practically, educational institutions are advised to strengthen job crafting practices, improve role clarity, and develop programs to enhance psychological resources. For future research, it is recommended that researchers adopt a longitudinal design and include a wider variety of educational institutions, so that the findings can be generalized more broadly.